1998
DOI: 10.1097/00000539-199807000-00011
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Inhaled Nitric Oxide on Postoperative Pulmonary Hypertension in Infants and Children Undergoing Surgical Repair of Congenital Heart Disease

Abstract: In a randomized double-blind study, inhaled nitric oxide selectively reduced pulmonary artery pressures in pediatric patients who developed pulmonary hypertension (high blood pressure in the lungs) immediately after cardiopulmonary bypass and surgical repair.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…Previous reports have highlighted the complexity of this phenotype (Russell, et al, 1998 ). In these previous reports, age at the time of surgery has been identified as an important factor in the development of elevated PAP, with younger children being at increased risk for this complication (Steinhorn and Fineman, 1999;Schulze-Neick et al, 2001).…”
Section: Discussionmentioning
confidence: 87%
“…Previous reports have highlighted the complexity of this phenotype (Russell, et al, 1998 ). In these previous reports, age at the time of surgery has been identified as an important factor in the development of elevated PAP, with younger children being at increased risk for this complication (Steinhorn and Fineman, 1999;Schulze-Neick et al, 2001).…”
Section: Discussionmentioning
confidence: 87%
“…17 Other studies demonstrate its effectiveness in the management of postoperative pulmonary hypertension in congenital heart disease patients. 18,19 Large multi-center trials have demonstrated that INO reduces the need for extracorporeal membranous oxygenation in newborns with persistent pulmonary hypertension. 20,21 Given the high cost of INO and the lack of demonstrable effect on mortality, utilization of a protocol to minimize costs without adversely affecting outcomes is prudent.…”
Section: Discussionmentioning
confidence: 99%
“…[6,7] The first reported randomized clinical trial was conducted by Russell et al, and included 35 patients with specific congenital heart defects and documented preoperative PH. [8] These patients, who were to undergo cardiopulmoFive Group I patients died in the early postoperative period; 2 had complete atrioventricular septal defect, 1 had TA, and 2 had hypoplastic left heart syndrome. One patient with complete atrioventricular septal defect and 1 with TA died from persistent pulmonary hypertensive crisis.…”
Section: Discussionmentioning
confidence: 99%